Mountain View School District Title III Class Profile, Level 5 - Mountain View School District, CA.; Mountain View School District, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Sample class profile record sheets, student profile record sheets, and diagnostic and mastery tests are included for level 5 of the Mountain View School District Bilingual Diagnostic-Prescriptive Mathematics Program. (MN)
Sponsoring Agency: Bureau of Elementary and Secondary Education (DHEW/OE), Washington, DC.
ERIC Note: For related documents, see SE 024 210-217; Contains occasional light and broken type.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Bilingual Students; Curriculum; Diagnostic Teaching; Diagnostic Tests; Elementary Education; Elementary School Mathematics; Instruction; Intermediate Grades; Mastery Tests; Mathematics Curriculum; Mathematics Education; Program Descriptions; Spanish Speaking; Tests; Mountain View School District CA; California; Tests/Questionnaires.